Post-traumatic stress, anxiety, and depression among oncology nurses during COVID-19 pandemic - Dung, Nguyen Thi (2022)
In December 2019, severe acute respiratory syndrome (SARS-CoV-2) was found in Wuhan, China, soon became a global pandemic and continued to spread with an alarming and unpredictable rate (Richards et al., 2020). Symptoms from patients with coronaviruses include mild cold, fever, muscle pain, cough, loss of taste or smell. Furthermore, 33% patients with COVID-19 have complications that are various from respiratory distress syndrome, septic shock and severe pneumonia (Al-Quteimat & Amer, 2020). According to a report from WHO, in 2020 COVID-19 viruses had infected 82 million people and killed at least 3 million people in the world (WHO, 2021). As of 6th September 2021, there have been over 220 million confirmed cases of COVID-19, including over 4.5 million deaths (WHO, 2021).